Have the public's expectations for antibiotics for acute uncomplicated respiratory tract infections changed since the H1N1 influenza pandemic? A qualitative interview and quantitative questionnaire study. Issue 2 (27th March 2012) - McNulty, Cliodna; Joshi, Puja; Butler, Chris C; Atkinson, Lou; Nichols, Tom; Hogan, Angela; French, David
Abstract : Objective: To investigate the effect of the H1N1 influenza pandemic on the public's expectations for a general practice consultation and antibiotic for acute respiratory illness. Design: Mixed methods. Participants: Qualitative interviews: 17 participants with acute respiratory tract infection (RTI) visiting English pharmacies. Face-to-face survey: about 1700 adults aged 15 years and older were recruited from households in England in January 2008, 2009 and 2011. Results: The qualitative data indicated that the general public had either forgotten about the 'swine flu' (H1N1 influenza) pandemic or it did not concern them as it had not affected them directly or affected their management of their current RTI illness. Between 2009 and 2011, we found that there was little or no change in people's expectations for antibiotics for runny nose, colds, sore throat or cough, but people's expectations for antibiotics for flu increased (26%–32%, p=0.004). Of the 1000 respondents in 2011 with an RTI in the previous 6 months, 13% reported that they took care of themselves without contacting their general practitioners and would not have done so before the pandemic, 9% reported that they had contacted their doctor's surgery and would not have done so before the pandemic and 0.6% stated that they had asked for antibiotics and would not have done so before the pandemic. In 2011, of 123 respondents with a young child (0–4 years) having an RTI in the previous 6 months, 7.4% requested antibiotics and would not have done so before the pandemic. Unprompted, 20% of respondents thought Tamiflu© (oseltamivir) was a vaccine. Conclusions: Expectations of the general public for a consultation or antibiotics with an RTI are similar now to before the H1N1 influenza pandemic; therefore, public antibiotic campaign messages and general practice advice to patients can remain unchanged. Parents with young children and those with personal experience of the H1N1 influenza are more likely to consult and will need more reassurance. The public need more education about Tamiflu©.